Strategi dan Capaian Indonesia dalam Memberdayakan Konten Lokal di Bidang Industri, Perdagangan, dan Pengadaan - Muhammad Iqbal Mutaqin (Jurnal Media Administrasi, 2024)
The Domestic Component Level (TKDN) Program is one of Indonesia's strategies in advancing its domestic industry. This local product protection policy has been implemented by Indonesia since the beginning of independence and has continued to be refined during subsequent governments. Although the TKDN policy has not succeeded in making Indonesia an industrial country like Korea, Indonesia's TKDN practice has not caused market failure as happened in Brazil. Indonesia needs to complement the TKDN policy with other industrial strengthening programs, so that the domestic industry becomes stronger and becomes the main pillar of national economic growth.